2020
DOI: 10.1177/1740774520901514
|View full text |Cite
|
Sign up to set email alerts
|

Discordant attitudes and beliefs about cancer clinical trial participation between physicians, research staff, and cancer patients

Abstract: Background/Aims Essential to bringing innovative cancer treatments to patients is voluntary participation in clinical trials but approximately 8% of American cancer patients are enrolled onto a trial. We used a domain-oriented framework to assess barriers to cancer clinical trial enrollment. Methods Physicians (MD, DO, fellows, residents) and research staff (physician assistants, nurse practitioners, staff and research nurses, clinical assistants, and program coordinators) involved in clinical research at a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 27 publications
(44 reference statements)
1
25
0
Order By: Relevance
“… 44 Other factors, including mistrust of the medical establishment and research due to historical racial injustice in clinical trials, may contribute to Black AYAs, and particularly Black men's relatively low enrollment in CTTs. 45 Similarly, the possibility of discordant attitudes 46 or implicit bias between provider and patient needs to be considered when determining what factors, either patient, provider or both, may contribute to low enrollment among Black AYA men.…”
Section: Discussionmentioning
confidence: 99%
“… 44 Other factors, including mistrust of the medical establishment and research due to historical racial injustice in clinical trials, may contribute to Black AYAs, and particularly Black men's relatively low enrollment in CTTs. 45 Similarly, the possibility of discordant attitudes 46 or implicit bias between provider and patient needs to be considered when determining what factors, either patient, provider or both, may contribute to low enrollment among Black AYA men.…”
Section: Discussionmentioning
confidence: 99%
“…There are, however, many other factors associated with trial participation, including patient trust in the medical system, medical literacy, socioeconomic status, educational background, and health care literacy. [31][32][33] These may all influence or be interrelated with the patient's own understanding of their illness, expectations of therapy, and trust in their oncologist. The physician approach to these patients may be different as well: in an effort to establish realistic expectations of treatment, discussions around goals of care may tend to occur earlier in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trial participation is associated with incorporating novel and experimental therapies, which may be considered a more aggressive approach to anticancer therapy. There are, however, many other factors associated with trial participation, including patient trust in the medical system, medical literacy, socioeconomic status, educational background, and health care literacy 31–33 . These may all influence or be interrelated with the patient's own understanding of their illness, expectations of therapy, and trust in their oncologist.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have also shown that HL physicians are less likely to recommend clinical trials to HLs relative to NHW patients [72]. Even when HLs are enrolled in clinical trials, they are more likely to not fully understand the aims of the clinical trial, perhaps because of cultural or language barriers, when compared with non‐Hispanic patients, a concerning realization with substantial ethical considerations [73]. Clinical trials in cancer care are the gateway to medical innovation, and patients of all genders, races, and ethnicities must be equally represented in an effort to ensure the results are applicable to all patients [74].…”
Section: Interpersonal and Systemic Implicit And Explicit Bias Effects On Health Equitymentioning
confidence: 99%